Auto-amputation of the Limbs and Early Colostomy’s Effect on Life Quality and Survival on the Patients with Severe Meningococcemia Related Purpura Fulminans: Two New and Different Approaches - Edin Botan; Tanıl Kendirli; Emrah Gün; Cansu Yöndem; Anar Gurbanov; Burak Balaban; Fevzi Kahveci; Savaş Serel; Esra Çakmak Taşkın; Halil Özdemir; Ergin Çiftçi; Erdal İnce (Journal of Pediatric Emergency and Intensive Care Medicine, 2022)

(untitled)
Purpura fulminans (PF) is a rare but fatal thrombotic disease caused by microvascular thrombosis due to coagulation disorder. Necrosis can progress to muscle and bone tissue contributing to late mortality and morbidity. A healthy 4-month-old girl and a 7-month-old girl had previously admitted to our intensive care unit with severe PF due to meningococcemia. Both patients had a severe and critical period in the pediatric intensive care unit and were supported with extracorporeal treatments. We opened colostomy for perineal infection because of large and deep skin lesions. In addition, we waited for a full auto-amputation involving all extremities instead of early surgical amputation. Both survived and acceptable limb function and some mobilization capacity were preserved. In conclusion, we think that early colostomy in severe perineal infections and autoamputation options in severe extremity involvement should be preferred in order to get better results.